2011
DOI: 10.2478/s13382-011-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and personality on the main cognitive processes in drivers

Abstract: Objectives: The purpose of this study is the evaluation of how the decline of cognitive abilities caused by aging is mode rated by biologically determined personality dimensions: Neuroticism (N) and Extraversion (E). Materials and Methods:The research was conducted with the participation of 160 men in good physical health, professional drivers, aged 20-70 (Mean = 40, SD = 11). Personality traits were measured using Eysenck's Personality Questionnaire -Revised (EPQR), while Ravens Progressive Matrices, Go/noGo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
1
3
0
3
Order By: Relevance
“…Moreover, our results are supported by recent studies which found significant associations between neuroticism, a construct which emotional instability is based on, and decreased cognitive performances (e.g., Sutin et al, 2019;Biernacki and Lewkowicz, 2020). Additionally, our results are supported by Biernacki and Tarnowski (2011), who found out that the sympathetic nervous system is activated more easily in subjects with higher emotional instability, resulting in a cascade of stress hormones being released and thus impairing cognitive performance (e.g., Wolf et al, 2001). Following this, the chronic experience of stress and the corresponding hormones are also linked to damaging the structure of brain regions, for example the hippocampus, which is responsible for cognitive tasks (e.g., Jackson et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, our results are supported by recent studies which found significant associations between neuroticism, a construct which emotional instability is based on, and decreased cognitive performances (e.g., Sutin et al, 2019;Biernacki and Lewkowicz, 2020). Additionally, our results are supported by Biernacki and Tarnowski (2011), who found out that the sympathetic nervous system is activated more easily in subjects with higher emotional instability, resulting in a cascade of stress hormones being released and thus impairing cognitive performance (e.g., Wolf et al, 2001). Following this, the chronic experience of stress and the corresponding hormones are also linked to damaging the structure of brain regions, for example the hippocampus, which is responsible for cognitive tasks (e.g., Jackson et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Przykładem takiego zastosowania symulatorów mogą być badania nad uwarunkowaniami powstawania błędów w kierowaniu pojazdów przez osoby starsze [10][11][12]. Badania te wykazały, że w przypadku starszych kierowców szczególną barierę stanowią warunki, które są związane z obciążeniem poznawczym (wykonywanie skrętu w lewo, włączanie się do ruchu, pokonanie nieoznakowanego skrzyżowania).…”
unclassified
“…Przykładem takiego zachowania jest wcześniejsze zaplanowanie podróży, uwzględnienie potencjalnych trudności na drodze itp. Takie planowanie pozwala więc na minimalizowanie ryzykownych decyzji [10][11][12].…”
unclassified
“…They reported that sensation-seeking was associated with greater driving violations and tickets, and undercontrolled temperament was associated with overall risky driving. Biernacki and Tarnowski (2011) studied 160 Polish drivers and found neuroticism had a moderating effect on driving performance, such that neuroticism increased the influence of age on declines in cognitive driving performance tasks. Finally, McPeek, Nichols, Classen, and Breiner (2011) studied a convenience sample of 50 older drivers, using an on-road assessment of driving behaviors and performance, self-rated driving ability, and the Myers-Briggs Type Indicator (MBTI) Step III instrument.…”
Section: Introductionmentioning
confidence: 99%